Unraveling the link between metabolic dysfunction-associated steatotic liver disease and osteoporosis: a bridging function of gut microbiota - Zhang, Jing; Sun, Zhen; Xu, Lili; Wang, Yunyang; Wang, Yangang; Dong, Bingzi (Frontiers in Endocrinology, 2025)
This review examines the strong association between metabolic dysfunction-associated steatotic liver disease (MASLD) and osteoporosis (OP), with a particular focus on the role of gut microbiota in linking these two disorders. Both MASLD and OP are closely linked to metabolic syndrome, and their pathogenesis involves multiple factors, such as inflammatory response, insulin resistance, altered intestinal permeability, and estrogen deficiency. Dysregulation of gut microbiota not only affects hepatic fat accumulation and bone metabolism disorders through metabolites, such as short-chain fatty acids, but also exacerbates systemic chronic inflammation by impairing the intestinal barrier function, thus accelerating the progression of both diseases. This article summarizes recent studies that highlight the central role of gut microbiota as a co-morbid factor in MASLD and OP, offering new perspectives for future diagnostic and therapeutic strategies.